Why do intelligent people care more about the environment? - Poškus, Mykolas Simas (Psichologija, 2021)
The present study investigates and provides support for the Savanna-IQ interaction hypothesis regarding pro-environmental values. Study 1 showed that the highest attained education level is a significant predictor of pro-environmental concern, while Study 2 showed that the trait of openness to experience plays a unique role in predicting biospheric values, but not other values, lending support for the Savanna-IQ interaction hypothesis. Acting to preserve the natural environment is an evolutionarily novel challenge, and therefore, is more actively addressed by individuals who more readily adopt novel ideas and seek out new ways of behaving.
Keywords: pro-environmental behavior; values; personality; openness to experience; intelligence